ROLE OF THE PHARMACIST IN MANAGING HIGH BLOOD PRESSURE OF HYPERTENSIVE PATIENTS IN PRIMARY CARE UNITS - DE SOUZA, JÚLIO EDUARDO PEREIRA; SILVA, EMERSON; NOVO, NEIL FERREIRA; SHIO, MARINA TIEMI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study was to evaluate the influence of pharmaceutical care on the control of high blood pressure (BP) in hypertensive patients. Methods: The study included thirty hypertensive patients from primary or secondary healthcare located in the south of São Paulo, Brazil. Results: The majority of patients was aged over 60 years (68.75%), non-smokers (90%), non-alcoholics (93.33%), did not practice physical activities (93.33%), and presented comorbidities and polypharmacy. The most common drug-related problems were drug-drug interactions, missed doses, incorrect frequency or time of administration, incorrect patient administration technique, and self-medication. The interventions used during the pharmaceutical consultations (PC) were based on the organization of medicines with tools such as a pillbox organizer (84.38%). A significant improvement in BP control (p<0.05) was observed when comparing BP measurements before and after the PC; however, the number of PCs did not influence the BP reduction. Conclusion: Patient guidance and a simple intervention favor better patient understanding of medication administration schedules.